Kinetic Studies of Nanostructured Food Packaging Materials - Rodriguez-Mercado, F; Torres-Mediano, A; Villegas-Vallejos, C (Elsevier, 2024)
The application of nanotechnology in the development of novel food packaging materials is an interesting strategy to obtain new materials in accordance with the current demands regarding the reduction of the use of plastics and environmental aspects. The incorporation of nanofillers into different polymer matrices to produce nanocomposites has been widely studied to modify the weight, heat resistance, flame retardation, and mechanical as well as barrier properties of plastic materials. Based on the relevance of understanding the thermal behavior of nanocomposites, this chapter will focus on the effect of nanofillers on the thermal degradation of polymers, mass transfer processes (migration), and material biodegradation. © 2024 Elsevier Inc. All rights reserved.